A novel anti-inflammatory polysaccharide from blackened jujube: Structural features and protective effect on dextran sulfate sodium-induced colitic mice. (30th March 2023) - Liu, Chuang; Qiu, Zhichang; Gu, Duanyin; Wang, Fangzhou; Zhang, Rentang
Graphical abstract: Highlights: An acidic polysaccharide (BJP-4) was isolated and purified from blackened jujube. BJP-4 mainly consisted of → 4)- α -l -Gal p A (1→, →5)- α -l -Ara f (1 → and → 4)- β -d -Gal p (1 →. BJP-4 greatly alleviated DSS-induced colitis in mice via altering gut microbiota. BJP-4 regulated key inflammation-related proteins and inflammatory cytokines. The oxidative status, intestinal epithelial barrier and SCFA level were improved. Abstract: This study explored the structural characteristics of the purified blackened polysaccharide fraction (BJP-4) and its potential to alleviate colitis. BJP-4 had a molecular weight of 1.24 × 10 5 Da and mainly consisted of → 4)- α -l -Gal p A (1→, →5)- α -l -Ara f (1 → and → 4)- β -d -Gal p (1 → residues. After the administration of BJP-4, the disease activity index of colitic mice was reduced by 40.38–50.96%, accompanied by increased colon length (30.00–62.50%) and ameliorated pathological damage. The mechanisms involved regulation of the intestinal microbiota and subsequent inhibition of the TLR4/MyD88/NF- κ B/NLRP3 pathway, balance of pro/anti-inflammatory cytokines and oxidative status, enhancement of epithelial barrier integrity and production of short-chain fatty acids. In particular, high-doses of BJP-4 significantly increased the abundance of beneficial bacteria (f_ Muribaculaceae, Lactobacillus and Lachnospiraceae _NK4A136_group, 0.78–1.04-fold) and suppressed the levels of harmful bacteria (o_ Clostridia _UCG-014, Bacteroides and Escherichia-Shigella, 32.30–90.42%). These findings revealed the anti-inflammatory effects and mechanisms of purified blackened polysaccharides, which facilitated their application in functional foods.